Permanent education in emergency reorganization hospital dentistry: convergente assistance research (Research, Society and Development, 2020)
The objective of this study is to reorganize the emergency work process based on permanent education, bringing practical implications to the multiprofessional team responsible for referring patients to emergency / dental urgency. Materials and method: convergent care research, approved by the ethics committee, opinion number 1,210,223. Data collection instruments: participant observation, semi-structured questionnaire and educational groups. Theoretical references were the National Policy for Permanent Education in Health and Agostinho de Hipona. Analysis based on Bardin's content analysis. Results: Four categories emerged, used as a reflection in making an instrument to facilitate referral to the dental sector and clarify the dentist's role in the emergency service. Conclusion: Health care levels can be organized based on the degree of severity of complaints that appear in the emergency, in order to more effectively address patients' dental complaints, as well as offering quality care. Recognizing the need and shortcomings of the work process also allowed for adding knowledge and providing advances for the multidisciplinary team about the role of the dentist in the emergency service and its duties.